2021
DOI: 10.3390/educsci11030125
|View full text |Cite
|
Sign up to set email alerts
|

The Soft Skills of Special Education Teachers: Evidence from the Literature

Abstract: The special education teacher is a key element in the development of the process of inclusive education. In this setting, soft skills have proven to be determinant in teachers’ educational action. However, those that best qualify their profile have not yet been identified. Therefore, this study aims to carry out a review of scientific production between the years 2010 and 2020. To this end, articles were selected using the following databases: ERIC, Scopus, Web of Science, and PsycINFO. Studies have been inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 57 publications
3
27
0
4
Order By: Relevance
“…Research on soft skills exists across different fields such as labor economics [7]; employability, workforce development, and human resource development [6,8]; management and communication [4,29]; and in industry or subject specific literature such as information technology [20,30]; STEM [31]; education [15], or library and information science [18]. In addition, not for profit agencies and government funded or public sector projects also conduct country, region, or industry specific research on soft skills [32][33][34].…”
Section: What Are Soft Skills?mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on soft skills exists across different fields such as labor economics [7]; employability, workforce development, and human resource development [6,8]; management and communication [4,29]; and in industry or subject specific literature such as information technology [20,30]; STEM [31]; education [15], or library and information science [18]. In addition, not for profit agencies and government funded or public sector projects also conduct country, region, or industry specific research on soft skills [32][33][34].…”
Section: What Are Soft Skills?mentioning
confidence: 99%
“…Accrediting bodies, such as ABET, have reiterated the need for engineering education programs to provide students opportunities to acquire a broader set of skills to improve their ability to collaborate, work in teams, and thrive in a globalized work environment [1]. Soft skills that were considered 'nice to have' within technical fields in the last century are moving to the 'need to have' category in the current century [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Fernandes et al confirmed that soft skills differ from one student to another. erefore, teachers must fully understand the strengths and weaknesses of the students they teach [5]. Bouillet and Kudek Mirosévic emphasized the importance of additional support in the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…They are love to children, positive perception of a learner with special educational needs, communication skills, pedagogical tact, cooperation with parents, colleagues, school administration. By carrying out a review of recent scientific literature, Fernandes, Jardim, and Lopes (2021) pointed out even more soft skills which scholars consider essential for special education teachers. They are resilience, reflexibility, empathy, collaborative work, self-efficacy, creativity, and effective communication.…”
Section: Significance Of the Studymentioning
confidence: 99%